Using Differentiation Method in the Inclusive Classroom (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the importance and effectiveness of the differentiation method in inclusive education environments. Research results indicate that the differentiation method plays a crucial role in meeting students' individual needs, improving their learning outcomes, and ensuring equal opportunities in inclusive classrooms. The article discusses strategies for implementing differentiation, its advantages, and challenges.